The Pattern of Juvenile Idiopathic Arthritis in a Single Tertiary Center in Saudi Arabia - Mohammad H. Al-Hemairi; Shatha M. Albokhari; Mohammed A. Muzaffer (International Journal of Inflammation)
Introduction. Juvenile Idiopathic Arthritis (JIA) is the most common chronic arthritis in children. Our aim is to describe demographic, clinical, and laboratory characteristics and treatment of JIA patients followed up in Pediatric Rheumatology clinic in a tertiary center in Saudi Arabia. Methods. Medical records of all patients who are followed up between January 2007 and January 2015 were retrospectively reviewed. Data were collected about demographic, clinical, and laboratory features and treatment. Results. Total patients were 82, males were 31 (37.8%), and mean age of JIA onset was 7.1 ± 3.6 yr. Mean follow-up duration was 2.67±1.6 yr. Systemic onset JIA (SoJIA) was the commonest (36.5%), followed by polyarticular in 29.2% and oligoarticular in 28%. Large and small joints are involved in 76 (92%) and 30 (36.6%), respectively. Main extra-articular feature was fever in 34 (41.4%). Uveitis was diagnosed in 7 (8.5%) and in 5 (21.7%) of oligoarticular JIA. Anemia was found in 49 (59.7%), high ESR in 45 (54.8%), and leukocytosis and thrombocytosis in 33 (40.2%). Positive ANA was found in 30 (36.5%) mainly in oligoarticular subtype as 12 (52%) patients (out of 23) had this positive test. 9 patients (10.9%) required NSAIDs only, 6 patients (7.3%) required NSAIDs and intra-articular steroids only, and 19 (23%) required NSAIDs, methotrexate, steroids, and biologics. Conclusion. SoJIA is the most common JIA subtype in our study. A population based rather than a single center study will give more details about JIA characteristics in Saudi Arabia